The Existence of Undergraduate Students in the Capital Market: Investment Interest in Stock - Yandes, Jufri; Putri , Dini Mustika Buana; Fathurrahman , Muhammad (Universitas Mohammad Husni Thamrin, 2025)
This study was conducted to examine the existence of undergraduate students in Bandar Lampung in terms of their interest in stock investment in the capital market, viewed from the perspective of investment knowledge and the use of online investment applications through the distribution of questionnaires. In today's digital world, technological developments have made it easier for the younger generation to access investments in a more practical and flexible manner. This application provides advanced features such as real-time monitoring, ease of transaction, and analytical tools that were previously only enjoyed by institutional investors. Using a quantitative approach through primary data and an ordinal Likert scale survey, the research results indicate that students' understanding of investment plays a significant role in increasing their interest in the stock market. Additionally, online investment applications contribute positively by providing user-friendly and educational platforms. The collaboration between knowledge and technology aspects has proven to strengthen undergraduate students' involvement in stock investment activities. Therefore, this study encourages the improvement of financial literacy and the integration of technology in investment education. Educational institutions are encouraged to enrich their curricula with investment-related materials and conduct practical training. Furthermore, collaborating with online investment app providers through seminars or training sessions is also seen as an effective strategy to encourage undergraduate students' interest in investing.